Writing an Impactful Introduction in Business and Management Research: Avoiding Common Pitfalls - Fodouop Kouam, Arthur William (International Journal of Scientific Research and Management (IJSRM), 2024)
A research study's impact and effectiveness heavily rely on the quality of its introduction. However, researchers often encounter common pitfalls that hinder the success of their introductions. This study addresses these challenges and provides guidelines for writing impactful introductions in academic research. By examining the common mistakes in introductions, such as lack of clarity, ineffective framing of the research problem, inadequate synthesis of previous studies, lack of engagement, and poor structure and organization, researchers can avoid these pitfalls and enhance the impact of their work. The study identifies these common pitfalls, analyzes their impact on the overall effectiveness of the study, and offers guidelines and recommendations for crafting engaging introductions. By following these guidelines, researchers can establish a strong foundation for their studies and effectively communicate their research goals to a broad audience, ultimately contributing to the success of their business and management research.